EVALUATION OF WATER QUALITY AND GROWTH PERFORMANCE OF RED TILAPIA (Oreochromis sp) IN CULTURE USING BIOFLOCK TECHNOLOGY - Putra, Iskandar; Rusliadi, Rusliadi; Masjudi, Heri; Alfinda, Rudi; Asiddiqqi, Hasby; Syahroni, Desty; Kurniawan, Ronal; Firmansyah, Rodhi; Yulindra, Ade (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
Water quality plays an important role in maintaining and increasing fish production. Tilapia (Oreochromis niloticus) is one of Indonesia's freshwater fish that has economic value. To increase production, tilapia cultivation is carried out intensively, characterized by high stocking density and provision of protein-rich feed. Good water quality control and feeding are key to the success of this intensive culture. Biofloc technology is one of the appropriate technologies for intensive tilapia rearing since fish can live at high densities and have a wide environmental tolerance. Biofloc technology is an alternative solution to problems in overcoming cultivation waste such as ammonia and nitrite. Based on the above, this study was conducted to determine the effectiveness of the biofloc system in converting ammonia compounds, improving water quality in the aquaculture environment, and understanding the relationship between water quality and tilapia growth. The research was conducted for 60 days to measure several water quality parameters, namely temperature, dissolved oxygen, acidity (pH), and ammonia, and to observe the growth parameters of tilapia. The treatment applied in this study was the addition of probiotics in feed with four treatments and three replications. The results showed that the biofloc system's water quality is tolerant to tilapia growth. The best growth results in treatment A with each value of absolute weight 14.70±0.10d, absolute length 6.70 ± 0.10d, specific growth rate 3.87±0.01c, and survival rate 100±0.00b.